Upper gastrointestinal complications following ablation therapy for atrial fibrillation. Issue 11 (19th May 2017) - Park, S.‐Y.; Camilleri, M.; Packer, D.; Monahan, K.
Abstract: Background: Following ablation therapy for cardiac arrhythmias, patients may develop upper gastrointestinal (UGI) symptoms. The vagus nerve is close to the atria and may be affected by ablating energy. Aim: To identify structural or functional complications in UGI tract following ablation for atrial fibrillation (AF) and clinical outcomes and association with vagal dysfunction. Methods: Using natural language processing of electronic medical records and an AF ablation database of 5380 patients treated during 17 years, we identified 40 patients with UGI complications. We evaluated vagal dysfunction by electrocardiogram (ECG) showing lack of sinus arrhythmia (variation in R‐R interval by ≥120 milliseconds, in presence of normal sinus P waves and constant P‐R interval). Key Results: Among 40 patients: (A) eight had structural GI complications confirmed by diagnostic tests: seven with esophageal ulcer/erosions and no signs of UGI bleeding and one developed esophagopericardial fistula (and survived with treatment); (B) 15 had functional UGI complications confirmed by objective motility tests. Nine had newly developed symptoms and six had aggravated symptoms; and (C) the remaining 17 had GI symptoms without relevant diagnostic results. Most UGI issues resolved spontaneously or with conservative treatment. However, 2 died several weeks after ablation procedure; cause of death was suspected atrioesophageal fistula or esophageal rupture. Vagal dysfunction persisted for 3 months in 13 and was transient in 8. Conclusions/Inferences: Although most GI issues resolved spontaneously, there should be a high index of clinical suspicion in patients with persistent symptoms. Vagal dysfunction may serve as a marker of more extensive tissue damage. Abstract : Following ablation therapy for cardiac arrhythmias, patients may develop upper gastrointestinal (UGI) symptoms. We aimed to identify the structural or functional complications in UGI tract following ablation for atrial fibrillation (AF) and clinical outcomes and association with vagal dysfunction. The overall incidence of UGI complications following ablation therapy for AF was extremely low (0.74% of the patient cohort) in a single center AF ablation database with highly experienced experts, and most UGI issues resolved spontaneously or with conservative treatment.